Biostratigraphy of the Upper Cretaceous Fort Munro Formation, Rakhi Gorge, Eastern Sulaiman Range, Pakistan: Geology - Zaheer, Arsalan; Ghazi, Shahid; Mehmood, Mubashir; Yaseen, Muhammad; Jehangir Khan, Muhammad; Serwar, Umair (Iraqi Journal of Science, 2022)
The Fort Munro Formation is well exposed along DG Khan-Fort Munro road, a type locality. The section was measured and sampled for the biostratigraphy, where it has a conformable lower contact with Mughalkot Formation and is underlain by the Pab Sandstone. The total observed thickness was 105 meters, and 26 samples were collected from top to the bottom at random intervals. Fifty thin sections were studied carefully, and five species of large benthic foraminifera, including Orbitoidestissoti, Orbitoidesapiculata, Orbitoides media, Orbitoideshottingeri, and Omphalocyclusmacroporus were identified along with miliolids. Gastropods, Bivalves and Echinoderms were also observed. Based on identified microfossils, the depositional environment of the formation is the inner ramp to the middle ramp deposited in the Campanian to Maastrichtian age.